2021
DOI: 10.1371/journal.pone.0251803
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota profiles of young South Indian children: Child sex-specific relations with growth

Abstract: Gut microbiota has been implicated as a modifier of childhood growth. Here, 16S rRNA sequencing-based fecal microbiota profiles of 18–24 month old Indian children were evaluated (n = 41), in relation to their anthropometric parameters, intestinal permeability, body composition and total energy expenditure. Pathway analyses were conducted to assess microbial functions related to stunting, underweight and wasting. The fecal microbiota was enriched in Prevotella 9, Bifidobacterium and Escherichia-Shigella. Weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 59 publications
2
21
0
2
Order By: Relevance
“…Ortiz et al also reported significant differences in the salivary microbiome between caries-active and caries-free boys and girls 51 . Gut microbiota studies have reported distinct sex-specific taxonomy and functional phenotypes 24 , 52 54 particularly in relation to neurodevelopment 55 . Some prepubescent, adolescent and adult studies have attributed these shifts or differences to the endocrine system 56 , suggesting an interplay between hormones, fat deposition and the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Ortiz et al also reported significant differences in the salivary microbiome between caries-active and caries-free boys and girls 51 . Gut microbiota studies have reported distinct sex-specific taxonomy and functional phenotypes 24 , 52 54 particularly in relation to neurodevelopment 55 . Some prepubescent, adolescent and adult studies have attributed these shifts or differences to the endocrine system 56 , suggesting an interplay between hormones, fat deposition and the microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…When classified according to the phylum, it was seen that the colony percentage of Firmicutes (38.6-44.7 16,46 vs 32.01-43.8 6,41 ) and Bacteroidetes (13.8-18.9 16,46 vs 20.08 6 ) was similar in both the Indian and Western populations. The percentage range for the colony percentage of Firmicutes and Bacteroidetes was narrow.…”
Section: Similarities and Differences Reported At Phyla Levelmentioning
confidence: 98%
“…Probiotics are live microbiota (especially bacteria and yeast) given as a supplement to prevent and/or correct dysbiosis as they help in normalizing the gut microbiota towards eubiosis. 10,[16][17][18][19] Traditionally, Indians have been moving to Western world countries for better education, career and health prospects. 20 Today, globalization has resulted in rampant movement of individuals from one country to another.…”
Section: Introductionmentioning
confidence: 99%
“…Bertambahnya usia balita juga mengindakasikan menurunnya jumlah bakteri menguntungkan yakni bifidobacterium bifidum dan bifidobacterium breve dalam saluran cerna. Tiga mikrobiota teratas jumlahnya dalam studi ini adalah golongan prevotella, bifidobacterium dan Escherichia-Shigella, dan Prevotella pada anak-anak sehat berusia 1-6 tahun ditemukan lebih banyak dalam feces yang dianalisis 23 .…”
Section: Jenis Dan Komposisi Mikrobiota Pada Anak Stunting Dan Normalunclassified
“…Hasil penelitian Vonaesch P, et., al (2018) mengkonfirmasi adanya dugaan jumlah bakteri enteropatogenik yang berlebihan dalam usus anak-anak dan bakteri yang terdapat pada orofaringeal yang berlebihan pada sampel tinja anak yang mengalami stunting. Hasil penelitian juga menemukan bahwa terdapat bakteri Escherichia coli, shigella sp, dan campylobacter sp pada sampel tinja anak-anak stunting, sedangkan pada anak-anak yang tidak mengalami stunting didominasi oleh bakteri-bakteri non patogen seperti lactobacillius, h.pylori, streptobacilli, bifidobacteriaceae pada lambung, duodenum, maupun sampel tinjanya walaupun juga terdapat bakteri patogen dalam jumlah sedikit 23,24 . Mikroorganisme yang menguntungkan mendominasi saluran cerna justru diketahui dapat membantu pencegahan gangguan pertumbuhan 25 .…”
Section: Jenis Dan Komposisi Mikrobiota Pada Anak Stunting Dan Normalunclassified